TRENDS IN REFORMING THE CONTENT OF EDUCATION OF PRESCHOOL CHILDREN AT THE KINDERGARTENS OF UKRAINE AT THE TURN OF THE XX-XXI CENTURIES - Nelly Lysenko (Vasyl Stefanyk Precarpathian National University, 2018)
The article deals with the problem of analysis the processes of updating the content of education and upbringing of children of preschool age in conditions of its transnationalization; the national and ethnonational component of preschool education of Ukraine as a counteraction to globalization has been updated; the problem of childhood ethnopedagogy is outlined. Key words: ethnopedagogy, pre-school childhood, national values, national traditions, personality, principles, directions of preschool education.